Agro-ecological Zones for Africa South of the Sahara - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
Agro-Ecological Zones (AEZ) for Africa South of the Sahara (SSA) were developed based on the methodology developed by FAO and IIASA. The dataset includes three classification schemes: 5, 8, and 16 classes, referred to as the AEZ5, AEZ8, and AEZ16, respectively.